In silico study of cis-acting elements revealing the plastid gene involved in oxidative phosphorylation are responsive to abiotic stresses - Shokri-Gharelo, Reza; Bandehagh, Ali; Mahmoudi, Bizhan; Moti-Noparvar, Pouya (Acta Biologica Szegediensis, 2017)
In order to study plastid gene response to abiotic stresses, the chloroplast genome of Brassica nigra and studied cis-acting elements were downloaded. All upstream regions of genes were determined and searched for the presence of known cis-acting elements. In these regions, 83 types of cis-acting elements were recognized. Unnamed elements (139 times), CAAT-box (96 times), and TATA-box (92 times) were in high frequency, whereas ATCC-motif, Box III, CE1, CE3, C-repeat/DRE, E2Fb, Gap-box, L-box, RY-element, and TGA-box occurred only one time. All of the cis-acting elements were grouped into seven categories, which 17% of cis-acting elements placed into abiotic and biotic-related elements. ARE (31 times) and LTR (21 times) elements were in high frequency. Among 42 genes with abiotic stress-related elements, 29 genes showed co-expression. Our results show that in response to anaerobic conditions and cold stress, chloroplast alters the genes-encoding proteins involved in complex I and V in oxidative phosphorylation pathway. This process, probably, is to reduce electron flow and convert NADPH and FADH forms to ATP form. These actions could decrease generating reactive oxygen species under stressful conditions. These findings could offer new insights on the strategies which chloroplasts take into account for preventing oxidative damage.